Green technology investment and channel selection in sustainable food supply chain based on blockchain technology - Yuting Zhang; Juan Shang (Frontiers in Sustainable Food Systems)
In the context of rapidly rising consumer demand for green food, this paper aims to systematically examine how green technology investment and blockchain technology influence the channel selections and operational decisions of members in the sustainable food supply chain. The question of whether conventional farmers should invest in green technology and utilize blockchain to attract more consumers is a critical issue amid the growing consumer demand for green food. We developed two sustainable food supply chain game models: Mode A (online-offline hybrid channel) and Mode H (e-commerce platform channel). These modes include conventional farmers, green farmers, offline supermarkets, e-commerce platforms, and consumers preference to green food. Based on these modes, we explore the operational strategies and profitability of each supply chain member in Scenario N (without blockchain technology) and Scenario B (with blockchain technology), after green farmers introduce blockchain technology in fixed-cost and unit-cost modes. The analysis reveals that when farmers invest in green technology and adopt blockchain technology, food greenness improves, and consumers' willingness to purchase green food increases. Our findings suggest that farmers' green technology are crucial for boosting sales and profitability, particularly in comparison to different distribution channels. We recommend that conventional farmers, who are uncertain about the cost of adopting blockchain for green farmers, should prioritize a mixed online-offline channel that does not include blockchain technology. Notably, offline supermarkets are generally opposed to the introduction of blockchain in the hybrid channel. However, when the fixed or unit cost of blockchain technology falls below a certain threshold, the sales model of “green technology + blockchain technology + e-commerce platform” becomes more profitable for farmers. The results presented in this paper provide new insights for food supply chain members on the benefits and operational choices of adopting blockchain technology and investing in green technology across different channels. Additionally, this paper highlights the significant impact of changes in the cost coefficients of green technology and commission rate on the sales quantity, wholesale prices, and profits of all participants, which is essential for the efficient operation of the sustainable food supply chain.